Chapter Femminielli and the city: urban space and non-binary gender identities in Naples - Cannella, Fabrizia (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This essay examines the interrelation between (peripheral) gender identity and (peripheral) urban space. The analysis focuses on the femminiello, a quintessentially Neapolitan non-binary subjectivity embodying a fluid sexual identity, performatively crossing across masculine and feminine, deeply connected to the territory where it originates-Naples' inner city and its low-income historic neighborhoods. Accordingly, the essay looks at the material and immaterial interrelations between urban space and the femminiello identity. Methodologically, the study is built on a qualitative approach based mainly on fieldwork interviews with three of the most prominent femminielli of the Neapolitan context: CiroCiretta, a recognized exponent of the femminielli community and among the founders of a cultural association devoted to spreading and preserving the ancient femminiello culture; Tarantina Taran, an iconic local figure dubbed as "Naples' last femminiello" in the city's Spanish Quarters; and Loredana, activist and secretary of Naples' Transsexual Association. The voices and stories of these three femminielli led us to read this non-binary gender identity in its relation to urban space, from different and complementary perspectives, which ultimately helped us trace a map of changing meaning and emerging forms of adaptation over time.